Implications of Fiscal Policy on Economic Growth - Mukhtar, Shaista; Ismail, Suraya; Tajuddin, Sheikh Ahmad Faiz Sheikh Ahmad (Pakistan Journal of Humanities and Social Sciences, 2024)
This study's objective is to evaluate Pakistan's growth-oriented fiscal policy elements from 1980 to 2023. This research uses secondary sources of data. The paper utilized the Autoregressive Distributed Lag (ARDL) model as analytical techniques to assess the short- and long-term dynamics between Pakistan's fiscal policy components and economic growth. According to our regression estimations, government expenditure slows down economic expansion, whereas taxes have a growth-oriented effect. The investigation also examined the significant and negative impact of debt. Interest rates, the control variable, strongly and adversely impact growth. The analysis concludes that shifting the balance of government spending from non-development to development goals is the only way to achieve sustained growth. In addition, the government ought to ensure political stability, create laws that will encourage business, build infrastructure using foreign loans, and use debt to develop human capital.